ZBrush Character Creation : Advanced Digital Sculpting - Spencer, Scott, 1975- (Indianapolis Wiley, 2011)
A stunning, content-rich update to this top-selling ZBrush guide! This second edition of ZBrush Character Creation has been fully updated for ZBrush 4, the newest version of this fascinating and popular 3D sculpting software. ZBrush enables users to create detailed organic models using a brush-based toolset and tablet
Include Index and Illustration
Keywords: ZBrush -- Computer graphics -- Computer animation